2014
DOI: 10.1021/jf504957c
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of Broccoli (Brassica oleracea var. italica) Myrosinase (β-Thioglucosidase Glucohydrolase)

Abstract: Myrosinase (β-thioglucosidase glucohydrolase, EC 3.2.1.147) from broccoli (Brassica oleracea var. italica) was purified by ammonium sulfate precipitation followed by concanavalin A affinity chromatography, with an intermediate dialysis step, resulting in 88% recovery and 1318-fold purification. These are the highest values reported for the purification of any myrosinase. The subunits of broccoli myrosinase have a molecular mass of 50-55 kDa. The native molecular mass of myrosinase was 157 kDa, and accordingly,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
31
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 25 publications
6
31
1
Order By: Relevance
“…Besides, since most authors use sinigrin in myrosinase studies, its use facilitates comparison with literature data. The highest specific activity of broccoli myrosinase and sinigrin was attained at pH 3.0, agreeing with Mahn et al [ 18 ], who reported that myrosinase activity was higher at acidic pH using sinigrin as substrate. Nevertheless, other authors reported that pH below 5 produced a structural destabilization of mustard seeds myrosinase.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Besides, since most authors use sinigrin in myrosinase studies, its use facilitates comparison with literature data. The highest specific activity of broccoli myrosinase and sinigrin was attained at pH 3.0, agreeing with Mahn et al [ 18 ], who reported that myrosinase activity was higher at acidic pH using sinigrin as substrate. Nevertheless, other authors reported that pH below 5 produced a structural destabilization of mustard seeds myrosinase.…”
Section: Discussionsupporting
confidence: 89%
“…Broccoli myrosinase has been poorly studied so far. This enzyme was purified for the first time by Mahn et al [ 18 ], and a preliminary characterization was reported. Recently, the cDNA nucleotide sequence of broccoli myrosinase was determined (Genbank ID: MF 461331); its amino acid sequence was deduced; and a three-dimensional model of its monomer was built (PMDB ID: 00811093) [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Broccoli ( Brassica oleracea ) is a popular vegetable because of its attractive green color and high nutritional value ( Martínez-Villaluenga et al, 2008 ). Many studies have focused on extracting bioactive metabolites from the edible parts of broccoli ( Assad et al, 2014 ; Mahn et al, 2014 ), extending the shelf life and maintaining the visual quality and content of bioactive compounds in broccoli florets ( Peng et al, 2015 ). However, the byproducts (in China about 200,000 tons of leaves and roots per year [ Su et al, 2005 ]) are left in the fields, leading not only to a waste of resources but also to a detrimental effect on the environment.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is supported by a study where a lower bioavailability and delayed appearance of ITC metabolites were observed in the biological fluids (plasma and urine) of individuals consuming a broccoli supplement lacking myrosinase versus those consuming fresh broccoli sprouts. These differences may partially be explained by the fact that plant-and aphid-derived, but not bacterial-derived, myrosinases belong to the glycoside hydrolase (GH) family GH1 and exhibit differences in their activity [102,103].…”
Section: Anti-cancer Properties Of Gl Metabolites and Their Bioavailamentioning
confidence: 99%